FLOROVSKY A. V. WORKS ON THE HISTORY OF RUSSIA, CENTRAL EUROPE AND HISTORIOGRAPHY: FROM THE ARCHIVAL HERITAGE / EDITED BY V. YU. AFIANI; INTRODUCTION BY M. V. KOVALEV, COMPILATION AND COMMENTARY BY V. YU. AFIANI, M. V. KOVALEV, E. V. KOSYREVA, T. N. LAPTEVA. ST. PETERSBURG: NESTOR-ISTORIYA, 2020. 576 P. ILLUSTRATIONS. - S. A. Romanenko; R. A. Klochkov (Гуманитарные и юридические исследования)
.